1997
DOI: 10.1023/a:1005884429760
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Three cDNA clones (pCel 10, pCel 20 and pCel 30), each encoding different endo-beta-1,4-glucanases in peach, were obtained by RT-PCR and their expression investigated by northern analysis during leaf and fruit abscission and during fruit development. This analysis allowed the detection of only the pCel 10-related mRNA. A 2.2 kb transcript accumulated in ethylene activated abscission zones of leaves and fruits, and ppEG1 (Prunus persica endoglucanase 1) the gene coding for pCel 10, was isolated and characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Compared to cellulases in other plants (Supplementary Fig. S7), LcCEL8 had higher similarity to abscission-related cellulases in citrus (CitCEL6; Merelo et al , 2017), peach (PpEG1; Trainotti et al , 1997), tomato (SlCel5; Kalaitzis et al , 1999), and pepper (cCel2; Trainotti et al , 1998b), while LcCEL2 was more closely related to cotton ( Gossypium hirsutum ) GhCel1 (Mishra et al , 2008) and peach PpEG4 (Trainotti et al , 2006). These data might not seem surprising if the comparisons refer only to the structure of the polypeptides rather than to their functions in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to cellulases in other plants (Supplementary Fig. S7), LcCEL8 had higher similarity to abscission-related cellulases in citrus (CitCEL6; Merelo et al , 2017), peach (PpEG1; Trainotti et al , 1997), tomato (SlCel5; Kalaitzis et al , 1999), and pepper (cCel2; Trainotti et al , 1998b), while LcCEL2 was more closely related to cotton ( Gossypium hirsutum ) GhCel1 (Mishra et al , 2008) and peach PpEG4 (Trainotti et al , 2006). These data might not seem surprising if the comparisons refer only to the structure of the polypeptides rather than to their functions in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of a cellulase-encoding mRNA induced by ethylene treatment was first reported in abscising bean leaves (Tucker et al , 1988). Since then, several studies have demonstrated that cellulase activity and gene expression are correlated with events in AZs during shedding of plant organs (in avocado, Tonutti et al , 1995; in tomato, del Campillo and Bennett, 1996; in pepper, Capsicum annuum , Trainotti et al , 1997; and in citrus, Kazokas and Burns, 1998). Cellulases are encoded by a multigene family, as confirmed in our study that identified 20 cellulase genes in the litchi genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This variability is the consequence of different genetic programmes, but also reflects the biochemical complexity of the plant cell wall structure [3]. A very important consequence of this complexity is that plants require a large set of different enzymes to carry out the physiological processes where modifications of the cell wall properties are required [4–9].…”
Section: Introductionmentioning
confidence: 99%